Surface Defect Engineering of CsPbBr3 Nanocrystals for High Efficient Photocatalytic CO2 Reduction. Issue 7 (13th May 2021) - Wang, Ji-Chong; Li, Nuoya; Idris, Ahmed Mahmoud; Wang, Jin; Du, Xinyi; Pan, Zhenxiao; Li, Zhengquan
Abstract : Converting CO2 into chemical fuels with sunlight is a very attractive approach to solve the greenhouse effect and fossil fuel crisis. Metal halide perovskite nanocrystals (NCs) have been identified as ideal semiconductor photocatalysts for photocatalytic CO2 reduction due to their unique properties, such as strong light absorption, low exciton binding energy, tunable bandgaps, and low cost. However, the pristine perovskite NCs suffering from inevitable defects, which lower their charge transfer efficiency and are detrimental to photocatalytic performance toward CO2 reduction. Herein, a facile approach to modify the surface defects of CsPbBr3 NC is demonstrated using tetrafluoroborate salts as defects treatment agent and loading Co 2+ as a cocatalyst. As a result, the optimized Co 2+ on the surface of defect‐free CsPbBr3 ‐BF4 shows a remarkable photocatalytic CO2 activity of 83.8 μmol g −1  h −1, which indicates that the surface modification can effectively suppress the undesired charge recombination in CsPbBr3 NC and promote its charge separation efficiency. This work provides an effective method to modify the surface defects of the CsPbBr3 NCs for high efficient photocatalytic CO2 reduction and broadens the photocatalytic applications of halide perovskites. Abstract : Surface modification of CsPbBr3 nanocrystals (NCs) is a promising approach to achieve efficient photocatalytic CO2 reduction. The BF4 - ions can strip the surface defects and suppress the charge recombination in CsPbBr3 NCs. The modified CsPbBr3 NCs exhibit improved photocatalytic activity and durability. This work provides a new method to tailor the photocatalytic properties of perovskite‐based photocatalysts.